Non-coding RNAs in Pancreatic Ductal Adenocarcinoma - Gong, Ruining; Jiang, Yueping (Frontiers in Oncology, 2020)
Non-coding RNAs (ncRNAs) are reported to be expressed in human cancers, including pancreatic ductal adenocarcinoma (PDAC). These ncRNAs affect the growth, migration and invasion of tumor cells by regulating cell cycle and apoptosis, as well as playing important roles in epigenetic processes, transcription and post-transcriptional regulation. It is still unclear whether alterations in ncRNAs influence PDAC development and progression. Because of this, analysis based on existing data on ncRNAs, which are crucial for modulating pancreatic tumorigenesis, will be important for future research on PDAC. Here, we summarize ncRNAs with tumor-promoting functions: HOTAIR, HOTTIP, MALAT1, lncRNA H19, lncRNA PVT1, circ-RNA ciRS-7, circ-0030235, circ-RNA_100782, circ-LDLRAD3, circ-0007534, circRHOT1, circZMYM2, circ-IARS, circ-RNA PDE8A, miR-21, miR-155, miR-221/222, miR-196b, miR-10a. While others including GAS5, MEG3, and lncRNA ENST00000480739, has_circ_0001649, miR-34a, miR-100, miR-217, miR-143 inhibit the proliferation and invasion of PDAC. Hence, we summarize the functions of ncRNAs in the occurrence, development and metastasis of PDAC, with the goal to provide guidance in the clinical diagnosis and treatment of PDAC.